ANALISIS POTENSI RISIKO K3 DENGAN METODE HIRARC (HAZARD IDENTIFICATION, RISK ASSESMENT AND RISK CONTROL) DI LABORATORIUM KIMIA PT TRIFA RAYA LABORATORIES - Elviana Arifahyani; Annisa Maharani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
A chemical laboratory is a workplace with a high potential for occupational hazards due to the use of chemicals, glassware, vials, laboratory instruments, and repetitive work activities. If these hazards are not systematically identified and controlled, they may increase the risk of occupational accidents and work-related illnesses, thereby affecting workers' safety and the continuity of laboratory operations. Therefore, risk analysis is necessary to identify potential hazards, assess risk levels, and determine appropriate risk control measures. This study aimed to identify occupational safety and health (OSH) hazards, analyze risk levels, and determine appropriate risk control recommendations in the Chemical Laboratory of PT Trifa Raya Laboratories using the Hazard Identification, Risk Assessment, and Risk Control (HIRARC) method. Data were collected through observation, FGD, and a review of the company's supporting documents. Risk assessment was conducted by determining the likelihood and severity values, followed by calculating the risk level based on the multiplication of these two parameters. The results identified 28 potential risks across 10 laboratory work activities, originating from chemical hazards, physical or mechanical hazards, ergonomic hazards, and waste-related hazards. The risk assessment showed that 23 risks were classified as low risk, representing 82.14% of the total identified risks, while 5 risks were classified as medium risk, accounting for 17.86%. No high-risk category was identified. Medium-level risks were primarily associated with cuts from glassware and vials, as well as exposure to chemical vapors or organic solvents that may cause irritation, dizziness, nausea, and respiratory disorders. Risk control recommendations were developed based on the Hierarchy of Controls, including elimination, engineering controls, administrative controls, and the use of appropriate personal protective equipment (PPE) according to the identified hazards. The findings of this study are expected to serve as a reference for the company in evaluating and improving the implementation of Occupational Safety and Health (OSH) in the Chemical Laboratory of PT Trifa Raya Laboratories.